The Effects of Stress on Tourniquet Application and CPR Performance in Layperson and Professional Civilian Populations. (May 2023) - Friberg, Marc; Jonson, Carl-Oscar; Jaeger, Victor; Prytz, Erik
Objective: The purpose of this study was to compare laypeople's and professional first responders' ability to perform tourniquet application and cardiopulmonary resuscitation (CPR) during calm and stressful circumstances. Background: Life-threatening bleeding is a major cause of death that could be prevented by fast and appropriate first aid interventions. Therefore, laypeople are now being trained in bleeding control skills, transforming them from bystanders to immediate responders. However, critics have questioned whether laypeople are able to perform during more stressful conditions. Method: Twenty-four laypersons and 31 professional first responders were tested in two conditions: a calm classroom scenario and a stressful scenario consisting of paintball fire and physical exertion. Stress and workload were assessed along with task performance. Results: The experimental manipulation was successful in terms of eliciting stress reactions. Tourniquet application performance did not decline in the stressful condition, but some aspects of CPR performance did for both groups. First responders experienced higher task engagement and lower distress, worry and workload than the laypeople in both the calm and stressful conditions. Conclusion: Stress did not affect first responders and laypeople differently in terms of performance effects. Stress should therefore not be considered a major obstacle for teaching bleeding control skills to laypeople. Application: Tourniquet application can be taught to laypeople in a short amount of time, and they can perform this skill during stress in controlled settings. Concerns about laypeople's ability to perform under stress should not exclude bleeding control skills from first aid courses for civilian laypeople.